In Vitro Assessment of the Cercaricidal Activity of Sida acuta Burm. F. and Sida rhombifolia Linn. (Malvaceae) Hydroethanolic Extracts, Cytotoxicity, and Phytochemical Studies. (10th January 2022) - Membe Femoe, Ulrich; Kadji Fassi, Joseph Bertin; Boukeng Jatsa, Hermine; Tchoffo, Yannick Leonel; Amvame Nna, David Carel; Kamdoum, Blaise Cédric; Njonte Wouamba, Steven Collins; Toussie Tchegnitegni, Billy; Tchaleu Ngadjui, Bonaventure; Sewald, Norbert; Ndjakou Lenta, Bruno; Tchuem Tchuente, Louis-Albert; et al.
Abstract : Despite the global efforts, schistosomiasis remains a public health problem in several tropical and subtropical countries. One of the major challenges in the fight against schistosomiasis is the interruption of the parasite life cycle. Here, we evaluated the anticercarial, cytotoxicity, and phytochemical profiles of Sida acuta (HE Sa ) and Sida rhombifolia (HE Sr ) hydroethanolic extracts (Malvaceae) . Schistosoma mansoni cercaria was collected from fifteen Biomphalaria pfeifferi -infected snails. Twenty-five cercariae were incubated in duplicate with different concentrations (31.25–1, 000  μ g/mL) of HE Sa or HE Sr . The cercaria viability was monitored at 30 min time intervals for 150 min, and the concentration-response curve of each plant extract was used to determine their respective lethal concentration 50 (LC50 ). Additionally, the cytotoxicity profile of each plant extract was evaluated on the Hepa 1–6 cell line at a concentration range of 15.625–1, 000  µ g/mL using the WST-8 assay method and its inhibitory concentration 50 (IC50 ) was calculated. Moreover, phytochemical characterization of each plant extract was carried out by HPLC-MS. Both extracts exhibited cercaricidal activity in a time- and concentration-dependent manner. At 30 min time point, HE Sa (LC50  = 28.41 ± 3.5  µ g/mL) was more effective than HE Sr (LC50  = 172.42 ± 26.16  µ g/mL) in killing S. mansoni cercariae . Regarding the cytotoxicity effect of both extracts, the IC50 of HE Sa (IC50  = 109.67  µ g/mL) was lower than that of HE Sr (IC50  = 888.79  µ g/mL). The selectivity index was 3.86 and 5.15 for HE Sa and HE Sr, respectively. Fifteen compounds were identified from HE Sa and HE Sr after HPLC-MS analysis. N-Feruloyltyramine, a polyphenol, and thamnosmonin, a coumarin, were identified in both extracts. HE Sa and HE Sr displayed cercaricidal activity and were not toxic on Hepa 1–6 cell line. Based on the selectivity index of these extracts, S. rhombifolia extract could be more effective on S. mansoni cercariae than S. acuta extract. This study could provide baseline information for further investigations aiming to develop plant-based alternative drugs against S. mansoni .